Outcomes of 27 gauge pars plana vitrectomy for a variety of posterior segment diseases - Muhammad Amer Awan; Shaheen, Fiza; Kholood Janjua (Journal of the Pakistan Medical Association, 2021)
Objective: To report our experience with 27 gauge (27G) pars plana vitrectomy (PPV) system for a variety of simple to complex posterior segment disorders Methods: Single center, Retrospective, Cohort study. Data of 665 eyes of 574 patients that underwent 27G PPV for a variety of indications from July 2015 to June 2019 at a tertiary care hospital was analyzed. Results: Common surgical indications included; Diabetic tractional retinal detachment (196, 29.5%), vitreous haemorrhage (191, 28.7%), full thickness macular hole (80, 12%), epiretinal membrane (66, 9.9%), endophthalmitis (26, 3.9%), tractional diabetic macular edema (14, 2.1%), ectopia lentis (11, 1.7%), dropped lens matter (13, 2%) and others (68, 10.2%). Mean operating time was 62 ± 37 minutes. With the exception of 2 cases where 20G fragmatome was utilized, no case required conversion to 20 gauge system while a 25G trocar was used for the silicon oil injection. Per-operative complications included; iatrogenic retinal tear (2 eyes, 0.3%) and supra choroidal silicon oil migration (1 eye, 0.15%). Post-operative complications were raised IOP (7 eyes, 1%), endophthalmitis (1 eye, 0.15%), hemorrhagic occlusive retinal vasculitis (1 eye, 0.15%) and retinal detachment (2 eyes, 0.3%). Mean Visual Acuity improved from 1.62 ± 0.68 logarithm of minimum angle of resolution (logMAR) to 0.4 ± 0.38 logMAR (P <0.001). Conclusion: With 3 months follow up time, 27 G PPV has proved to be a safe and effective system for both simpler and complex retinal pathologies requiring significant surgical manipulation. Continuous...